2020
DOI: 10.1098/rstb.2019.0578
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the demographic history of Japan using ancient oral microbiota

Abstract: While microbial communities in the human body (microbiota) are now commonly associated with health and disease in industrialised populations, we know very little about how these communities co-evolved and changed with humans throughout history and deep prehistory. We can now examine these communities by sequencing ancient DNA preserved within calcified dental plaque (calculus), providing insights into the origins of disease and their links to human history. Here, we examine ancient DNA preserved within dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 101 publications
2
29
0
Order By: Relevance
“…On the other hand, we did not identify significant differences between ancient samples that were grouped based on sex, age, and lifestyle. This result is consistent with previous studies [ 8 , 38 , 43 ] suggesting the relative stability in the composition of the oral microbiome at definite time points.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, we did not identify significant differences between ancient samples that were grouped based on sex, age, and lifestyle. This result is consistent with previous studies [ 8 , 38 , 43 ] suggesting the relative stability in the composition of the oral microbiome at definite time points.…”
Section: Discussionsupporting
confidence: 93%
“…S9). The differential abundance of these AMR gene families was also observed in other prehistoric and historic samples from the literature (7,9,22,35), thus suggesting that methodological factors associated with laboratory procedures were most likely not responsible for the differences observed. The rpoC gene family was also discussed given its higher abundance in the ancient samples, except for those from Weyrich's study (9) (Datasets S12 and S13 and SI Appendix, Fig.…”
Section: Methodsmentioning
confidence: 64%
“…Tannerella forsythia may be a new example of an established outcome of colonialism, the fostering of a range expansion of more virulent pathogens. Eisenhofer et al [23] investigate human oral microbiomes of ancient Japan, specifically Jomon hunter-gatherers and Edo agriculturalists, who represent two time periods, each with distinct lifestyles. Despite the expectation that such a major lifestyle change should result in a microbiome shift as detected in prior gut microbiome studies [24], Eisenhofer et al [23] observed that the microbiome variation changed little between these periods, with a noteworthy exception of Edo-period differences between the sexes, which they propose reflects traditional cultural practices.…”
mentioning
confidence: 99%
“…Eisenhofer et al [23] investigate human oral microbiomes of ancient Japan, specifically Jomon hunter-gatherers and Edo agriculturalists, who represent two time periods, each with distinct lifestyles. Despite the expectation that such a major lifestyle change should result in a microbiome shift as detected in prior gut microbiome studies [24], Eisenhofer et al [23] observed that the microbiome variation changed little between these periods, with a noteworthy exception of Edo-period differences between the sexes, which they propose reflects traditional cultural practices. In the third article, Achtman & Zhou [25] discuss recently developed bioinformatic tools for investigating microbial diversity in metagenomic datasets, and they use these to examine the oral microbiome from ancient dental calculus in addition to modern saliva and dental calculus samples across a broad geographical region.…”
mentioning
confidence: 99%